Pengaruh Komunikasi dan Budaya Kerja terhadap Kinerja Pegawai: Studi Empiris Pada BKPSDM Kabupaten Konawe Utara - Hafipah; Andi Hendra Syam; Mohamad Nur (Journal of Sustainable Business Hub, 2020)
This research was conducted with the aim of: 1) Analyzing the influence of communication on performance North Konawe Regency Personnel and Human Resources Development Agency (BKPSDM) employees, 2) Analyzing the influence of the Work Culture of North Konawe District Personnel and Human Resources Development Agency (BKPSDM) employees and 3) Analyzing Human Resource Development (BKPSDM) North Konawe Regency. This research uses primary data and secondary data. The population is 71 employees of the North Konawe District Personnel and Human Resources Development Agency (BKPSDM) in September 2020. The sample was 71 people using the sensus method. The contents of the data include: observation, interviews, questionnaires and documents. The analytical method used is multiple linear regression with SPSS program version 24. The results of the study share that simultaneously the Communication and Work Culture variables share their posts and share their posts with BKPSDM of North Konawe Regency. Partially the work culture variable is the dominant influence compared to the communication variable.